2022
DOI: 10.3934/geosci.2022018
|View full text |Cite
|
Sign up to set email alerts
|

Artificial coral reefs as a localised approach to increase fish biodiversity and abundance along the North Bali coastline

Zach Boakes,
Alice E Hall,
Georgia CA Jones
et al.

Abstract: <abstract> <p>Coral reefs face worldwide decline from threats such as climate change, destructive fishing practices, overfishing and pollution. Artificial reefs have shown potential as a method to mitigate localised habitat loss and biodiversity decline on degraded coral reefs. The health of coral reefs in Indonesia and their associated faunal populations have displayed a downward trend in recent decades, and community-managed non-government organisations have started using artificial reefs to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Previous studies reported that biofouling occurs more rapidly on the rough surface of the artificial reef than on the smooth surface. The increasing attachment of marine biota using diversity index indicators can reach 20% on artificial reefs using cockle shell waste material compared to pure concrete materials [25]- [27]. The closing event of community service in Mutiara Beach is captured by a memorable moment in FIGURE 17.…”
Section: Evaluating the Results Of Trainingmentioning
confidence: 99%
“…Previous studies reported that biofouling occurs more rapidly on the rough surface of the artificial reef than on the smooth surface. The increasing attachment of marine biota using diversity index indicators can reach 20% on artificial reefs using cockle shell waste material compared to pure concrete materials [25]- [27]. The closing event of community service in Mutiara Beach is captured by a memorable moment in FIGURE 17.…”
Section: Evaluating the Results Of Trainingmentioning
confidence: 99%